Corporate Sustainability Practices & Reporing: A Case of Malaysian REITs and Property Listed Companies - Zahid, Muhammad; Ghazali, Zulkipli; Ur Rahman, Haseeb (International Journal of Economics and Financial Issues, 2016)
This paper investigated the quality of reporting regarding different dimensions (economic, environmental, social) of corporate sustainability (CS) in Malaysia. The paper examined the quality of CS disclosure on the basis of Global Reporting Initiative (GRI) in a sample of 113 listed companies from REITs and property sectors for four years i.e. from 2010-2013. The data collected from websites and annual reports of these companies exhibit variations in quality and disclosure of different CS dimensions. The paper found that environmental dimension was less while social dimension was a highly focused aspect of CS. Moreover, most of the companies report sustainability for the sake of mere compliance to the relevant regulations. This paper is unique in terms to focus all the dimensions of CS as most of the previous literature addressed these separately. Moreover, being a first comprehensive study, particularly after 10th Malaysian Plan (2011-2015), the paper has important findings for regulators, academia, researchers and other stakeholders. Keywords: Corporate sustainability, Listed Companies, Malaysia JEL Classification: M000